Effects of various hydrogenated temperatures on photocatalytic activity of mesoporous titanium dioxide - Soo, Chan Wai; Lai, Chin Wei; Pan, Guan Ting; Yang, Thomas Chung Kuang; Lee, Kian Mun; Yusop, Rahimi Muhammad; Juan, Joon Ching (Institution of Engineering and Technology, 2018)
Hydrogenated titanium dioxide (H-TiO2) has drawn much research attention in the photocatalysis society since it has significantly improved solar absorption and enhanced photocatalytic activity. Nevertheless, the key factor that leads to the enhanced photocatalytic performance of H-TiO2 is still debatable. To clarify this issue, the structural properties of H-TiO2 and its effects on photogenerated charges are investigated. Mesoporous H-TiO2 was subjected to different hydrogenation temperatures rate under the flow of purified H2 gas and its photocatalytic activities are evaluated by reactive black 5 photodegradation. The H-TiO2 pretreated at different temperatures seems to have a detrimental effect on photocatalytic activity as compared with that of untreated H-TiO2. Further investigations reveal that H-TiO2 treated at high temperature can cause the formation of less photoactive rutile phase and agglomeration that leads to the inhibition of their photocatalytic activity.